Pre-commercialisation grant evaluation session 2 and commercialisation seedfund evaluation - Laili, Zulkepeli (Penerbit UMP, 2014)
Evaluations for the pre-commercialisation grant (Session Two) and commercialisation seed fund for 2014 were held at Universiti Malaysia Pahang (UMP) Research and Innovation Department (JP&I) meeting room on August 12, 2014.